Development of Guided Inquiry Learning Tools using Socio-Scientific Issue to Train Critical Thinking Ability and Care for The Environment of Students - Wulansari, Fitria Wahyu; Dewi, Novi Ratna (Universitas Negeri Semarang, 2022)
Learning cannot be separated from the existence of learning tools. Learning devices are components that are used as a reference for implementing the learning process. The learning process requires appropriate models and strategies to train students' knowledge and attitudes. This study aims to determine the characteristics and feasibility of guided inquiry learning tools using the socio-scientific issue (SSI) to train critical thinking skills and care for the environment of students. The learning tools developed consist of a syllabus, lesson plans, student worksheets, and evaluation tools for question sheets. The characteristics of the learning tools are (1) containing guided inquiry (2) containing socio-scientific issues (SSI), (3) training critical thinking skills, and (4) training environmental care. The research model used is ADDIE (analyze, design, development, implementation, and evaluations) which is modified by using 4 of the 5 stages of ADDIE. The results of the feasibility analysis of the learning device components from the validation results and the teacher/student readability questionnaire obtained very feasible criteria and the evaluation tool of the question sheet was valid. The results obtained indicate that the development of guided inquiry learning tools using the socio-scientific issue (SSI) is feasible to use in the learning process